2000
DOI: 10.1007/pl00013428
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol modulates lipoprotein cytotoxicity in obstructive nephropathy

Abstract: Oxidative stress in unilateral ureteral obstruction (UUO) contributes to the development of glomerular and tubulointerstitial lesions. The present study investigated whether oxidized low-density lipoprotein (oLDL) contributes to the pathogenesis of kidney injury in UUO, and whether alpha-tocopherol modulates such cytotoxicity and promotes repair. Male Sprague-Dawley rats weighing 100-125 g were assigned to three groups of 6 animals each: (1) sham, regular chow; (2) UUO, regular chow; and (3) UUO, alpha-tocophe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
2
26
0
1
Order By: Relevance
“…Furthermore, Kida et al and Sato et al determined that a positive linear relationship exists between tubular dilatation and tubular epithelial apoptosis in UUO mice (18). Increased ROS, lipid peroxidation, and compromised antioxidants were previously found in a number of studies using obstructed rodent kidneys (6,24,35,48), and ROS have been suggested to impair the integrity of the glomerular basement membrane, reduce podocyte proteoglycan de novo synthesis, and stimulate factors promoting ECM deposition, including TGF-␤ 1 (9), as similarly observed in the present study. Overall, these results corroborate our results in the RTEC model system.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, Kida et al and Sato et al determined that a positive linear relationship exists between tubular dilatation and tubular epithelial apoptosis in UUO mice (18). Increased ROS, lipid peroxidation, and compromised antioxidants were previously found in a number of studies using obstructed rodent kidneys (6,24,35,48), and ROS have been suggested to impair the integrity of the glomerular basement membrane, reduce podocyte proteoglycan de novo synthesis, and stimulate factors promoting ECM deposition, including TGF-␤ 1 (9), as similarly observed in the present study. Overall, these results corroborate our results in the RTEC model system.…”
Section: Discussionsupporting
confidence: 86%
“…[15][16][17][18][19][20] In addition, studies have reported that the antioxidant vitamin E and the antihypercholesterolemic agent probucol reduce nephrotoxicity. 21,22) However, few drugs with antioxidant activity are clinically available, and such drugs are not used for antioxidant purposes. In this study, we investigated the physiological action and mechanism of action of ESE on ADR nephropathy, which was considered to be strongly influenced by oxidant stress.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of renal TGF-ß1 expression was also demonstrated in some reports [75,76], but not in all [77]. Nephroprotective effects of ·-tocopherol include attenuation of renal structural and functional alterations in IgA nephropathy [75], retardation of development of glomerulosclerosis in a remnant kidney model [78] and many others (table 2) [67,68,75,[78][79][80][81][82][83][84]. In one uncontrolled clinical study, vitamin E administration decreased proteinuria in children with FSGS [85].…”
Section: Vitaminsmentioning
confidence: 99%